MANTAN ORDO KAPUSIN PROVINSI MEDAN DARI TAHUN 2000 HINGGA 2012: KAUSA PENGUNDURAN DIRI - Simanullang, Gonti (LOGOS, 2017)
It is an undeniable fact that the number of young Capuchin candidates whohave not been ordained priests from 2000 to 2012 resign, at their own choice anddecision, from the Capuchin Order of Medan Province. This fact raises thequestion â€œWhy did they withdraw from the Capuchin Order of the Province ofMedan?â€ To answer this question we used exploratory research and methods ofexit interview and exit questionary. It was found that there is a causalrelationship between the increasingly firm belief in the inability to live celibateand the reason for withdrawing from the Capuchin Order of the Province ofMedan. This finding is useful for finding ways that can help the CapuchinOrder of the Province of Medan be able to monitor early gifts of celibacy orfamily life in candidates, such as when candidates are still in postulancy ornovitiate.